Dynamic symbolic data structure repair - Hussain, Ishtiaque; Csallner, Christoph (2010 ACM/IEEE 32nd International Conference on Software Engineering, 2010)
Generic repair of complex data structures is a new and exciting area of research. Existing approaches can integrate with good software engineering practices such as program assertions. But in practice there is a wide variety of assertions and not all of them satisfy the style rules imposed by existing repair techniques. I.e., a "badly" written assertion may render generic repair inefficient or ineffective. In this paper we build on the state of the art in generic repair and discuss how generic repair can work effectively with a wider range of correctness conditions. We motivate how dynamic symbolic techniques enable generic repair to support a wider range of correctness conditions and present DSDSR, a novel repair algorithm based on dynamic symbolic execution. We implement the algorithm for Java and report initial empirical results to demonstrate the promise of our approach for generic repair.